Catheter Ablation of Long-Lasting Accelerated Idioventricular Rhythm in a Patient with Mild Left Ventricular Dysfunction - Takanao Mine; Mamoru Hamaoka; Hideyuki Kishima; Tohru Masuyama (Case Reports in Cardiology)
A 35-year-old woman with long-lasting accelerated idioventricular rhythm (AIVR) exhibited palpitation and dyspnea on exertion and mild left ventricular (LV) dysfunction during followup. Symptoms appeared 10 years after the AIVR was first noted, and she underwent catheter ablation for curative therapy of AIVR after 12 years. Radiofrequency ablation of the anteroseptal site of the LV at the earliest activation terminated rhythm. An echocardiogram, taken 1 month after discharge, subsequently revealed that the left ventricular wall motion had normalized. This is a rare case of long-lasting AIVR with mild LV dysfunction.